2008
DOI: 10.1016/j.schres.2007.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Communication disturbances, working memory, and emotion in people with elevated disorganized schizotypy

Abstract: This study examined whether people with elevated disorganized schizotypy would differ from control participants on characteristics associated with disorganization symptoms in schizophrenia and also whether disorganized schizotypy was associated with problems processing emotion. People with disorganized schizotypy (n = 32) exhibited greater communication disturbances (CD) than control participants (n = 34) for emotionally negative topics but not for positive topics. In addition, the disorganized group exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 43 publications
7
54
0
Order By: Relevance
“…A metaanalysis from our laboratory found that working memory deficits are among the most prominent differences in cognitive abilities between PS and non-PS groups, yet remain at a small effect size level (Chun et al, submitted for journal). In line with this finding, Kerns and Becker (2008) observed that individuals with PS demonstrated both working memory deficits and increases in odd speech in a stressful speech condition when compared to a non-PS group. They also observed that group differences in odd speech in this stressful condition were no longer significant when working memory deficits were controlled for.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…A metaanalysis from our laboratory found that working memory deficits are among the most prominent differences in cognitive abilities between PS and non-PS groups, yet remain at a small effect size level (Chun et al, submitted for journal). In line with this finding, Kerns and Becker (2008) observed that individuals with PS demonstrated both working memory deficits and increases in odd speech in a stressful speech condition when compared to a non-PS group. They also observed that group differences in odd speech in this stressful condition were no longer significant when working memory deficits were controlled for.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have observed small to medium effect size differences in odd speech when comparing PS and non-PS groups (Kerns and Becker, 2008;Minor and Cohen, 2010). These differences may be partially accounted for by cognitive deficits, particularly in working memory, as speech disorder is thought to reflect a failure in neurocognitive processing .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Compared to a nonschizotypy group, significant group differences only emerged once pleasant and unpleasant valence was introduced. Precedence for this finding has been provided by formal thought disorder studies, where significantly larger increases in disorganization have been observed in psychometric schizotypy groups from baseline to unpleasant valence conditions (Kerns & Becker, 2008;Minor, Cohen, Weber, & Brown 2011; but also see Minor & Cohen, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…One way to examine the inXuence of these confounds is to conduct research on people with schizophrenia who are taking medication as well as people who have never received medication (e.g., MacDonald et al, 2005). In addition, another way to remove these confounds is to conduct research with people at-risk for schizophrenia who do not yet have the disorder and are not receiving medication (e.g., Kerns & Becker, 2008). Another way to examine associations between cognitive deWcits and symptoms without these confound is human analogue research in which cognitive manipulations attempt to experimentally cause an increase in schizophrenia symptoms Kerns & Berenbaum, 2003;Sher & Trull, 1996).…”
Section: Schizophrenia Heterogeneitymentioning
confidence: 99%